Instrução ao sósia e análise do discurso docente: representações sociais de língua/linguagem do professor dos anos iniciais - Marques, Fátima Carla Furtado Silva (2024)
The aim of our research is to analyze, based on teacher discourse, the representations of language teaching in the elementary school years. The study was carried out with a 5th grade teacher from the public school system in Fortaleza and with the working group made up of Portuguese language teachers from the elementary school. We aimed to understand how the teacher's language activity involves/updates their concepts and didactic choices. As a methodological procedure for the research application, we used a survey questionnaire and the method of Instructions to the double (CLOT, 2010). The theoretical basis of our research will be divided into the following themes: Portuguese Language Teaching and the elementary school teacher (MOITA LOPES, 2011; MILLER, 2013; CELANI, 2009).; Dialogic Discourse Theory (BAKHTIN, 1997, 2010; SOBRAL, 2009; FARACO, 2017; FIORIN, 2018; RIBEIRO, 2010); Clinical Activity (CLOT, 2006; 2010; 2021; AMIGUES, 2004; MACHADO, 2002; SOUZA-E-SILVA, 2004) and Social Representations Theory (MOSCOVICI, 2005; 2012; JODELET, 2001; MARKOVA, 2006; 2017). In order to analyze the linguistic activity, we structured our study around the theoretical-methodological device of the IaS (BATISTA; RABELO, 2013; CLOT, 2006, 2010; ODDONE; RE, BRIANTE, 1981) and the theory related to the Clinical Activity (AMIGUES, 2004; CLOT, 2006, 2010; MACHADO; LOUSADA, 2010; TARDIF, 2010). The procedures for compiling the corpus of our research were carried out in five steps: 1. Questionnaire survey; 2. Instruction to the double; 3. Transcription of the IaS dialogues; 4. Production of a commentary-text; 5. Discussion session (feedback to the group). By means of the exotopic practice of talking about her teaching practice, putting herself in the place of "the other" (double), the teacher produced statements that we used in our interpretative analysis. This contemplative practice provided by the IaS gave the teacher a surplus of insight so that she could perceive something that she couldn't realize in the same practice she was describing. The IaS has developed a dialogic environment through the teaching group strength. We have seen an improvement in spaces of analysis of teaching practice. This theoretical-methodological approach is oriented towards and constructed through processes of (co)analysis of teaching practice, which make it possible to access specific aspects of this type of practice, which can lead to its development and (trans)formation analyses. It provides an opportunity to access the teaching practice, through the speech of the teachers themselves, which, in an exotopic and alteritarian movement, promotes subjective and intersubjective relations, leading to the construction of a reflective and dialogic analysis of their practice.